Left Bundle Branch Area Pacing in a Giant Atrium With Atrial Standstill: A Case Report and Literature Review - Zheng, Jing; Yang, Qingye; Zheng, Jiasheng; Chen, Qiang; Jin, Qizhi (Frontiers in Cardiovascular Medicine, 2022)
Atrial standstill (AS) is a rare condition defined by the lack of atrial electrical and mechanical activities. It is usually clinically manifested as symptomatic bradycardia, which requires permanent pacemaker (PPM) implantation. Traditional right ventricular apical pacing causes electrical and mechanical dyssynchrony resulting in left ventricular dysfunction, heart failure, and arrhythmias. As a novel physiological pacing strategy, left bundle branch area pacing (LBBaP) has demonstrated effectiveness and safety in recent years, but its application in exceptional conditions is rarely reported. We report the case of a 47-year-old female, who was diagnosed with AS complicated with a giant atrium, and successfully received a single-chamber PPM with LBBaP.